2019
DOI: 10.5114/pedm.2019.87709
|View full text |Cite
|
Sign up to set email alerts
|

Levothyroxine supplementation for obesity-associated thyroid dysfunction in children: a prospective, randomized, case control study

Abstract: Introduction: The specific treatment of thyroid dysfunction associated with simple obesity (SO) in children is controversial. Material and methods: Fifty-one children having SO (BMI ≥ 2 Z-score) aged 6-12 years with elevation of serum thyroid stimulating hormone (TSH) (4-10 mIU/l) with or without alterations in serum triiodothyronine (T3) or thyroxine (T4) were randomised to receive either routine weight management intervention (group 1, n = 25) or additional low dose levothyroxine (~0.5 μg/kg/day) (group 2, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…[ 16 ] Treatment of obesity-associated subclinical hypothyroidism has almost no influence on the body weight and lipid profile. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] Treatment of obesity-associated subclinical hypothyroidism has almost no influence on the body weight and lipid profile. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the characteristics of the studies included in the analysis. There are studies performed with subjects from Italy (14,16,17), France (8,15), Israel (11,22), Turkey (12,18), Germany (13,19,20), the Netherlands (9), Swiss (10), United States (21), and India (23).…”
Section: Resultsmentioning
confidence: 99%
“…In 5 studies, a psychological intervention was added to the nutritional plus exercise intervention (10,13,14,19,20). One study performed the 3 interventions plus levothyroxine supplementation (23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is associated with hypothyroidism (especially the subclinical form) in children, as described above. A 6-month, randomised trial in 51 obese children with TSH 4-10 mIU/L (with or without abnormalities of other thyroid hormones) showed that administration of LT4 vs. no additional treatment, alongside weight loss interventions, had no significant effect on BMI or lipid abnormalities [66]. A similar study, where LT4 was or was not added to a behavioural intervention for obesity, reported similar results [67].…”
Section: Subclinical Hypothyroidismmentioning
confidence: 93%